2008
DOI: 10.1186/1745-6215-9-1
|View full text |Cite
|
Sign up to set email alerts
|

The ACTIVE (Acute Cholecystitis Trial Invasive Versus Endoscopic) study: Multicenter randomized, double-blind, controlled trial of laparoscopic (LC) versus open (LTC) surgery for acute cholecystitis (AC) in adults

Abstract: Background: In some randomized trials successful laparoscopic cholecystectomy for cholecystitis is associated with an earlier recovery and shorter hospital stay when compared with open cholecystectomy. Other studies did not confirm these results and showed that the potential advantages of laparoscopic cholecystectomy for cholecystitis can be offset by a high conversion rate to open surgery. Moreover in these studies a similar postoperative programme to optimize recovery comparing laparoscopic and open approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 9 publications
0
41
0
1
Order By: Relevance
“…Only one study (25) reported common bile duct injuries with 1 injury for each group among 200 cholecystectomies. The other 3 studies [13,23,27] reported no bile duct injuries.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Only one study (25) reported common bile duct injuries with 1 injury for each group among 200 cholecystectomies. The other 3 studies [13,23,27] reported no bile duct injuries.…”
Section: Resultsmentioning
confidence: 97%
“…Four studies reported data on bile leakage [23,26,28,29] and only one was randomized [23]. 326 patients were treated with OC and 343 with LC (Fig.…”
Section: Bile Leakagementioning
confidence: 99%
“…A search of the literature published between January 2013 and December 2016, after the publication of TG13, and using the keywords “acute cholecystitis,” “laparoscopic cholecystectomy,” and “open cholecystectomy” returned papers on one systematic review and one randomized controlled trial. In terms of the incidence of surgical complications, the team producing these guidelines performed a meta‐analysis using a random‐effects model on four randomized controlled studies because the systematic review used a fixed‐effects model even though various differences in the research papers were detected. The odds ratio for the incidence of surgical complications is 0.34 (95% CI: 0.07–1.60), which suggests that laparoscopic surgery may be effective but the difference between Lap‐C and open cholecystectomy is not statistically significant (Fig.…”
mentioning
confidence: 99%
“…The populationbased outcome research showed also lower morbidity and mortality [103]. An additional trial, published after that consensus [104], confirmed those findings. A further randomized controlled study demonstrated that the laparoscopic cholecystectomy caused less surgical trauma and immunosuppression (by measuring serum C-reactive protein and tumor necrosis factor-a -TNF-a-secretion of peripheral blood mononuclear cells) and also confirmed that it was associated with a shorter hospital stay [105] (LE2).…”
Section: Acute Cholecystitismentioning
confidence: 63%